PLANT GROWTH RESPONSE ONLY (LACTUCA SATIVA L.) ON MEDIA USING VERMIKOMPOS WASTE CULTIVATION OF MUSHROOM CUSHION
’l7Iis research is done to know the influences of the maturity vemUcompost level of mushroom cultivated waste on the growth of se/ada, to know the influences of the combination between soil and vermicompost of mushroom cultivated waste on the growth of selada, to know the influences of interaction between vermicompost maturity level and the combination between soil and vermicompost on the growth of selada and to know what the vermicompost of mushroom cultivated waste can be used as organicfertiliser of seiada cultivation. This research is done to know the response of selada crop planted on dijJerentmaturation vermicompost media. The preparation that must be done before areproduce vermicompost and breeding of selada crop and analise ofvermicompost.The dependent variabel of this research is maturation vermicompostlevel (composted during 1month), half maturity (composted duringtwo months) and mature (composted during 3 months). The combination between soil and compost is 2:1, 3:1 and 4:1. The independent variabel is the growth of Selada that include wet weight (gram), high of crop (em), number of leaf (piece), and dry weight of crop (gram). The data of the research result of crop growth analysed using completly random design factorial. When there is a significant different continued with Duncan Multiple Range Test